A Study on Food Handlers' Knowledge and Practices of Personal Hygiene during Kumbh Mela, 2015-16 at Nashik, India - Balaji D Almale; Sudha G Ayyar; Supriya Dhakne-Palwe; Rakesh N Patil (Medsci Publications, 2018)
Introduction- This study was conducted in the 'Kumbh Mela' at Nashik where the 'Annachatras' of 'Sadhugram' cater food de- mands of large number of inmates and devotees. This increased  the need for maintenance of food and personal hygiene of the food handlers. Hence it was decided to assess knowledge and practices regarding personal hygiene of food handlers. Methods- Observational study of 62 food handlers, with struc- tured pre-designed proforma was undertaken. Study was carried out among 3 Akhaadas of Nashik during Sept-Dec 2015. After in- formed consent from participants, information on socio- demographic data, knowledge and practices about food and per- sonal hygiene was obtained. A general physical examination to as- sess personal hygiene was also undertaken. Results-Most of the food handlers (85.5%) had heard and 83.9% had knowledge of transmission of diseases by food. There was less use of gloves (19.4%); hair cover (17.7%) and face mask (14.5%). There was acceptable level of personal hygiene mainly clean hairs (95.2%), clean cut nails (83.8%) and clean hands (88.7%). There was no association of education with knowledge, practice or level of personal hygiene. Conclusion- The study revealed that most of food handlers had knowledge of food borne diseases and observed personal hygiene.